Corona virus, tariffs, trade wars and supply chain evolutionary design. Issue 10 (6th July 2020) - Handfield, Robert B.; Graham, Gary; Burns, Laird
Abstract : Purpose: Using the constructal law of physics this study aims to provide guidance to future scholarship on global supply chain management. Further, through two case studies the authors are developing, the authors report interview findings with two senior VPs from two multi-national corporations being disrupted by COVID-19. This study suggests how this and recent events will impact on the design of future global supply chains. Design/methodology/approach: The authors apply the constructal law to explain the recent disruptions to the global supply chain orthodoxy. Two interviews are presented from case studies the authors are developing in the USA and UK – one a multi-national automobile parts supplier and the other is a earth-moving equipment manufacture. Specifically, this is an exploratory pathway work trying to make sense of the COVID-19 pandemic and its impact on supply chain scholarship. Findings: Adopting the approach of Bejan, the authors believe that what is happening today with COVID-19 and other trade disruptions such as Brexit and the USA imposing tariffs is creating new obstacles that will redirect the future flow of supply chains. Research limitations/implications: It is clear that the COVID-19 response introduced a bullwhip effect in the manufacturing sector on a scale never-before seen. For scholars, the authors would suggest there are four pathway topics going forward. These topics include: the future state of global sourcing, the unique nature of a combined "demand" and "supply shortage" bullwhip effect, the resurrection of lean and local production systems and the development of risk-recovery contingency strategies to deal with pandemics. Practical implications: Supply chain managers tend to be iterative and focused on making small and subtle changes to their current system and way of thinking, very often seeking to optimize cost or negotiate better contracts with suppliers. In the current environment, however, such activities have proved to be of little consequence compared to the massive forces of economic disruption of the past three years. Organizations that have more tightly compressed supply chains are enjoying a significant benefit during the COVID-19 crisis and are no longer being held hostage to governments of another country. Social implications: An implicit assumption in the press is that COVID-19 caught everyone by surprise, and that executives foolishly ignored the risks of outsourcing to China and are now paying the price. However, noted scholars and epidemiologists have been warning of the threats of pandemics since the severe acute respiratory syndrome (SARS) virus. The pundits would further posit that in their pursuit of low-cost production, global corporations made naive assumptions that nothing could disrupt them. Both the firms the authors have interviewed had to close plants to protect their workforce. It was indicated in the cases the authors are developing that it is going to take manufacturers on average one month to recover from 4–6 days of disruption. These companies employ many thousands of people, and direct and ancillary workers are now temporarily laid off and face an uncertain future as/when they will recover back to normal production. Originality/value: Using the constructal law of physics, the authors seek to provide guidance to future scholarship on global supply chain management. Further, through two case studies, the authors provide the first insight from two senior VPs from two leading multi-national corporations in their respective sectors being disrupted by COVID-19. This study is the first indication to how this and recent disruptive events will impact on the design of future global supply chains. Unlike the generic work, which has recently appeared in HBR and Forbes, it is grounded in real operational insight.